2013
DOI: 10.1155/2013/984626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water, Sanitation, and Hygiene Interventions on Improving Health Outcomes among School Children

Abstract: Purpose. This review was done to explore the impact of water treatment, hygiene, and sanitary interventions on improving child health outcomes such as absenteeism, infections, knowledge, attitudes, and practices and adoption of point-of-use water treatment. Methods. A literature search was conducted using the databases PubMed and Google scholar for studies published between 2009 and 2012 and focusing on the effects of access to safe water, hand washing facilities, and hygiene education among school-age childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 24 publications
(63 reference statements)
4
84
0
Order By: Relevance
“…The poor access to sanitary water supply is a common problem in over 850 million people worldwide. one of the most diseases caused by a lack of access to clean water and sanitation facilities are diarrhea which contribute to the mortality rate of about 1.9 million and new diarrhea cases estimated at 4 billion annually especially among children (10). So sufficient sanitary water and water fountains are necessary to prevent the spread of diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…The poor access to sanitary water supply is a common problem in over 850 million people worldwide. one of the most diseases caused by a lack of access to clean water and sanitation facilities are diarrhea which contribute to the mortality rate of about 1.9 million and new diarrhea cases estimated at 4 billion annually especially among children (10). So sufficient sanitary water and water fountains are necessary to prevent the spread of diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bad economic situation and the weaknesses of the municipality infrastructures such as the sewers systems force people not to take care of these cesspits, which regular flooding forms waste water pools in the roads and yards. It is worth to mention that people always discharge the cesspits and the pools manually (18).…”
Section: Methodsmentioning
confidence: 99%
“…Statistics indicated that of the 0·71 million annual diarrheal deaths, 90% occur in children, mainly from developing countries (17). The global burden of disease and mortality rates could be reduced by about 9.1% and 6.3%, respectively, if rapid success is attained in facilitating access to water, sanitation, and hygiene facilities (18,19). Many studies reported that quality of water, sanitation systems and hygiene behavior are all connected to waterborne disease frequency in the communities (2,3,(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The family composition is prevalently 4-6 family members as expressed by 723 students quantified as 65%, some 219 or 19% of the pupils stated 7 and more family members, and 175 or 16% asserted family members of 1-3. (Joshi &Amadi, 2013). …”
Section: Ethical Considerationmentioning
confidence: 99%
“…In addition, researches at Queensland University in Brisbane, Australia reveal that users have a strong preference for using paper towels and that "hand hygiene adherence would possibly decrease if paper towels are not available in wash rooms. Joshi and Amadi (2013) concluded access to hand washing instructions and facilities improved primary school attendance. There is a critical need for targeting health messages through schools in order to reach the most susceptible schoolchildren.…”
Section: Knowledge Practice and Facilities Utilization In Hand Hygienementioning
confidence: 99%